2021
DOI: 10.3390/genes12040522
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Topology of DNA Associated with Circulating Extracellular Vesicles Released during Exercise

Abstract: Although it is widely accepted that cancer-derived extracellular vesicles (EVs) carry DNA cargo, the association of cell-free circulating DNA (cfDNA) and EVs in plasma of healthy humans remains elusive. Using a physiological exercise model, where EVs and cfDNA are synchronously released, we aimed to characterize the kinetics and localization of DNA associated with EVs. EVs were separated from human plasma using size exclusion chromatography or immuno-affinity capture for CD9+, CD63+, and CD81+ EVs. DNA was qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…For precision studies a pool of venous plasma from six healthy subjects before (PRE exercise sample) and after exercise (POST exercise sample) was used. The samples were randomly selected from another study collective, which was included in Neuberger et al, 2021 26 . The healthy adults were aged between 21 and 25 years (23.4 ± 1.4) showing a mean BMI of 21.9 ± 1.1 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For precision studies a pool of venous plasma from six healthy subjects before (PRE exercise sample) and after exercise (POST exercise sample) was used. The samples were randomly selected from another study collective, which was included in Neuberger et al, 2021 26 . The healthy adults were aged between 21 and 25 years (23.4 ± 1.4) showing a mean BMI of 21.9 ± 1.1 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…That is, two labs may not be able to identify comparable EV populations using comparable instruments. These finding underline the need for standardization of EV isolation protocols and methodologies and are discussed in an international expert consortium, which has already provided a guideline for flow cytometry based-EV analyses [9] . Adding another layer of complexity, Marca also discussed the overlap of EV analysis with lipoprotein particles and other protein complexes from human samples.…”
Section: Ev In Clinical Diagnostics -Performing Reliable Ev Biomarker Analysismentioning
confidence: 93%
“…Currently several studies have investigated elements of the response of circulating small EVs to acute aerobic (Frühbeis et al, 2015;Guescini et al, 2015;Bertoldi et al, 2018;D'Souza et al, 2018;Lovett et al, 2018;Oliveira et al, 2018;Whitham et al, 2018;Brahmer et al, 2019;Yin et al, 2019;Karvinen et al, 2020;Rigamonti et al, 2020;Gao et al, 2021;Neuberger et al, 2021;Zhang et al, 2021), resistance (Annibalini et al, 2019;Just et al, 2020;Vechetti et al, 2021) or combined plyometric and downhill running (Lovett et al, 2018) exercise. Most of these studies have attempted to characterize circulating small EVs separated from plasma (Frühbeis et al, 2015;Guescini et al, 2015;D'Souza et al, 2018;Lovett et al, 2018;Whitham et al, 2018;Annibalini et al, 2019;Brahmer et al, 2019;Yin et al, 2019;Just et al, 2020;Rigamonti et al, 2020;Gao et al, 2021;Neuberger et al, 2021;Vechetti et al, 2021), although four studies have separated small EVs from serum (Bertoldi et al, 2018;Oliveira et al, 2018;Karvinen et al, 2020;Zhang et al, 2021).…”
Section: Changes In the Small Extracellular Vesicle Profile In Response To Acute Exercisementioning
confidence: 99%
“…Ten studies have employed a single methods approach for determining small EV enrichment using either NTA (Lovett et al, 2018;Annibalini et al, 2019;Just et al, 2020;Rigamonti et al, 2020;Vechetti et al, 2021), flow cytometry (Bei et al, 2017;Gao et al, 2021), or Western blot (Bertoldi et al, 2018;Neuberger et al, 2021;Zhang et al, 2021) to estimate small EV enrichment in response to acute aerobic (Bei et al, 2017;Bertoldi et al, 2018;Rigamonti et al, 2020;Gao et al, 2021;Neuberger et al, 2021), resistance (Annibalini et al, 2019;Just et al, 2020;Vechetti et al, 2021), or combined plyometric and downhill running (Lovett et al, 2018) exercise. Each of these studies, except one (Lovett et al, 2018), observed an increase in their respective measures in within preparations of small EVs taken after exercise, which potentially indicates an exerciseinduced enrichment in small EVs.…”
Section: Changes In the Small Extracellular Vesicle Profile In Response To Acute Exercisementioning
confidence: 99%